Effects of Exercise Type on Hemodynamic Responses and Cardiac Events in ACS Patients - Kim, Chul; Lim, Young-Joon; Kim, Chul-Hyun; Kim, Young-Joo; Jee, Haemi (Journal of Physical Therapy Science, 2014)
[Purpose] This study investigated the effects of mid, and high exercise intensities on hemodynamic responses and cardiac events during two exercise types of treadmill exercise (TM) and cycle ergometer exercises (CE) in patients with acute coronary syndrome (ACS). [Subjects] Patients who had percutaneous coronary intervention (PCI) for ACS and were participating in cardiac rehabilitation program were included. [Methods] The patients were assessed for hemodynamic responses, cardiac events, and rate of perceived exertion (RPE) with target heart rates of 60% and 85% heart rate reserve (HRR) during TM and CE. [Results] Maximum systolic blood pressure (SBP), diastolic blood pressure (DBP), RPE, and rate pressure product (RPP) measured during CE were significantly higher than their values in TM at the same exercise intensities. The highest SBP was shown at 85% HRR during CE. SBPmax to SBPmax ratios obtained during the graded exercise test (GXT) showed that all %SBPmax were significantly greater in CE than in TM at the same exercise intensities. Out of 102 patients, cardiac events occurred in 8 at 85% HRR during CE, and 1 at 85% HRR during TM. Patients with cardiac events (CE-E) had significantly higher %SBP, %RPP, and RPE at 85% HRR than those without events (CE-NE) during CE. [Conclusion] Prescribing exercise based on the intensity obtained in a treadmill GXT may expose patients to cardiovascular complications such as higher RPP, higher exercise intensity, and cardiac events during CE.